The Effect of Green Accounting, Environmental Performance, Independent Commissioner, and Firm Size on Firm Value: Evidence from Basic Materials Sector Companies Listed on the Indonesia Stock Exchange (2021-2024) - Najwa Hanaiudia Ramadhani; Roy Budiharjo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study was motivated by the inconsistencies in the results of perivous studies and the phenomenon of declining firm value in the basic materials sector. The analysis focuses on assessing the extent to which green accounting implementation, environmental performance, board independence represented by independent commissioners, and firm size influence firm value. Employing a quantitative approach, this study relies exclusively on secondary information extracted from annual reports, sustainability reports, and PROPER environmental assessment reports covering the 2021–2024 period. Sample selection followed a purposive sampling strategy, producing a balanced panel dataset consisting of 24 publicly listed firms and 96 firm-year observations. The proposed relationships were examined using panel data regression estimated through the Fixed Effects Model (FEM). The findings suggest that neither green accounting, environmental performance, nor board independence exerts a statistically meaningful influence on firm value. In contrast, firm size is found to be negatively associated with firm value.